PROJECT: RECOMMENDATIONS ON TREATMENT OF RHEUMATOID ARTHRITIS DEVELOPED BY ALL-RUSSIAN PUBLIC ORGANIZATION «ASSOCIATION OF RHEUMATOLOGISTS OF RUSSIA» – 2014 (PART 1) - E. L. Nasonov; V. I. Mazurov; D. E. Karateev; G. V. Lukina; E. V. Zhilyaev; V. N. Amirdzhanova; Yu. V. Muraviyov; N. V. Tchichasova (Научно-практическая ревматология, 2015)
Authors report new recommendations of All-Russian Public Organization «Association of Rheumatologists of Russia» (ARR) on treatment of rheumatoid arthritis (RA), which adapts contemporary concept accepted in the respective field of pharmacotherapy known as «Treat to Target». According to it, the main objective of RA pharmacotherapy is a remission (or low disease activity). To achieve it, disease modifying anti-rheumatic drugs (DMARD) should be administered to all RA patients as early as possible, with efficacy monitoring and therapy correction according to the disease activity. Special attention has been paid to the use of methotrexate (MTX) as «the gold standard» of RA pharmacotherapy and the key component of «Treat to Target» strategy. Early MTX administration (including subcutaneous injections) should become an obligatory component of RA treatment at all stages of the disease. If MTX is not efficient or not well tolerated (including subcutaneous form of the drug) as monotherapy or combined with conventional DMARD, biological agents should be used. Those include TNFα inhibitors, antagonist of interleukin-6 receptor (Tocilizumab), anti-B-cell drugs (Rituximab) and agents blocking T-cell activation (Abatacept). Tofacitinib therapy (JAK inhibitor) is indicated in patients who are resistant to conventional DMARDs and biologics. All biologics and Tofacitinib are more effective in combination with MTX (or other DMARD).